2021
DOI: 10.1007/s11882-021-01020-z
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Fiber Pectin: Health Benefits and Potential for the Treatment of Allergies by Modulation of Gut Microbiota

Abstract: Purpose of Review The incidence of allergies is increasing and has been associated with several environmental factors including westernized diets. Changes in environment and nutrition can result in dysbiosis of the skin, gut, and lung microbiota altering the production of microbial metabolites, which may in turn generate epigenetic modifications. The present review addresses studies on pectin-mediated effects on allergies, including the immune modulating mechanisms by bacterial metabolites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 177 publications
(194 reference statements)
1
56
1
Order By: Relevance
“…In recent years, the relationships between the fermentation properties of dietary fibers and their structural characteristics have attracted increasing attention (Bang et al, 2018; Beukema et al, 2020; Blanco‐Pérez et al, 2021; Ferreira et al, 2018; Lin et al, 2021; Y. Zhang et al, 2021). In vitro anaerobic fermentation that mimics the mammalian colon has been regarded as a useful tool to support studies of diet–gut microbiota interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the relationships between the fermentation properties of dietary fibers and their structural characteristics have attracted increasing attention (Bang et al, 2018; Beukema et al, 2020; Blanco‐Pérez et al, 2021; Ferreira et al, 2018; Lin et al, 2021; Y. Zhang et al, 2021). In vitro anaerobic fermentation that mimics the mammalian colon has been regarded as a useful tool to support studies of diet–gut microbiota interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation with the three kinds of pectin induced slightly higher content of propionic acid than glucose and the blank control (Figure 7B), and no significant alterations were observed in isovaleric acid within different groups (Figure 7E). In recent years, the relationships between the fermentation properties of dietary fibers and their structural characteristics have attracted increasing attention (Bang et al, 2018;Beukema et al, 2020;Blanco-Pérez et al, 2021;Ferreira et al, 2018;Lin et al, 2021;. In vitro anaerobic fermentation that mimics the mammalian colon has been regarded as a useful tool to support studies of diet-gut microbiota interactions.…”
Section: Pectin With Various Degrees Of Esterification Influenced Scf...mentioning
confidence: 99%
“…[ 11 ] Immunomodulatory effects on allergies seen with pectin intake were related to increased concentrations of SCFA produced by the gut microbiota. [ 12 ] Supplementation with fructo‐oligosaccharides and galacto‐oligosaccharides changed the gut microbiota while also having antidepressant effects on mice. [ 13 ] According to a recent meta‐analysis, these dietary fibers could also increase Bifidobacterium and Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation reported that natural polysaccharides could positively regulate gut microbiota owing to their prebiotic properties [5]. The gut microbiota is one of the critical regulatory factors in in ammatory responses.…”
Section: Introductionmentioning
confidence: 99%